Misdiagnosis or missed diagnosis? Cone-beam computed tomography-aided multidisciplinary management of maxillary central incisor with palatogingival groove - R Kurinji Amalavathy; K M Vidya; Sonali Nabil Sarooshi; Hrudi Sundar Sahoo (Wolters Kluwer Medknow Publications, 2021)
Palatogingival groove is a developmental anomaly that is most often seen on maxillary incisors, with a predilection for lateral incisors. It begins in the central groove and can extend to varying lengths and depths into the root. This groove can communicate with the pulp internally and periodontium externally, thereby establishing a milieu for the development of complex endodontic-periodontic lesion. In this article, we report multidisciplinary management of a maxillary central incisor, which was mistaken to be a vertical root fracture instead of a palatogingival groove. We also discuss the significance of early recognition of this lesion, differential diagnosis, and it's interdisciplinary management with the aid of cone-beam computed tomography.